ANALISIS KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO LIKUIDITAS, RASIO SOLVABILITAS, DAN RASIO PROFITABILITAS (Studi Komparasi PT. Bank Negara Indonesia Tbk, PT. Bank Mandiri Tbk, Dan PT. Bank Rakyat Indonesia Tbk, Periode 2012-2015) - Manueke, Billy Boy Rilmonth (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
This study aims to determine financial performance based on banking financial ratios used in this study to PT. Bank Mandiri, Tbk, PT. Bank Negara Indonesia, Tbk, PT. Bank Rakyat Indonesia, Tbk in 2014-2017 and compared the financial performance of these three banks. Using the ratio analysis technique can provide an assessment of the financial performance of a company and can also help describe the trends and patterns of the company so that it can show the opportunities or risks of the company being analyzed by the analyst. Financial ratio analysis becomes very important, especially for interested parties in the company. The analytical tool used in this research is Financial Ratio which includes Liquidity Ratio, on the results of the study indicate the average liquidity ratio of PT. Bank Mandiri, Tbk in 2012 - 2015 is very good because it has met the standards set by Bank Indonesia. Bank Negara Indonesia, Tbk is not good because it does not meet the standards set by Bank Indonesia. ROE PT. Bank Negara Indonesia, Tbk amounting to 16.15%.